1967
DOI: 10.1161/01.res.20.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Right Duct Lymph Flow in Experimental Heart Failure Following Acute Elevation of Left Atrial Pressure

Abstract: We measured the pulmonary lymph flow in dogs with mild congestive failure before and after acute elevation of the left atrial pressure to 40 cm of water. The creation of an aorticocaval fistula and the administration of desoxycorticosterone trimethylacetate and a salt enriched diet in 6 dogs produced mild pulmonary edema and partial expansion of the pulmonary lymphatics 10 to 12 days postoperatively. Elevation of the left atrial pressure to 40 cm of water under pentobarbital anesthesia led to an immediate incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This has been demonstrated in an animal model. 31 Finally, chronic alterations in diastolic compliance of the left ventricle can limit increases in filling pressure during exercise. This would prevent pulmonary congestion and increase exercise capacity.…”
Section: Cardiac Medicationsmentioning
confidence: 99%
“…This has been demonstrated in an animal model. 31 Finally, chronic alterations in diastolic compliance of the left ventricle can limit increases in filling pressure during exercise. This would prevent pulmonary congestion and increase exercise capacity.…”
Section: Cardiac Medicationsmentioning
confidence: 99%
“…In the first set of studies of this report hydrostatic pressures were elevated by circulatory overload, while oncotic pressure remained essentially unchanged; in the second set, oncotic pressure was reduced under conditions of relatively stable hydrostatic pressure. Previous studies by others have been shown that the respective procedures produce marked elevation in pulmonary lymph flow rates from lungs, in vivo, in response to a presumed but not directly measured increase in rates of outward filtration (Uhley et al, 1967;Zarins et al, 1978).…”
mentioning
confidence: 88%
“…However, homeostasis of the extravascular fluid volume of the airways and lung also depends on effective lymph drainage from the lung. The pumping pressure in the lymphatic vessels close to the external jugular vein is approximately 17 cm H 2 O [56]. Thus, when this pressure is exceeded in the jugular veins, it is likely that pulmonary lymphatic drainage will be compromised, leading to an increase in the extravascular fluid volume and the appearance of respiratory symptoms.…”
Section: Exercise In Elderly People With Hfmentioning
confidence: 99%